Diagnostic protocol for gestational diabetes mellitus (GDM) (IADPSG/ADA, 2011): influence on the occurrence of GDM and mild gestational hyperglycemia (MGH) and on the perinatal outcomes - Sirimarco, Mariana Pinto [UNESP]; Guerra, Helena Maciel [UNESP]; Lisboa, Eduardo Guimarães [UNESP]; Vernini, Joice Monalisa [UNESP]; Cassetari, Bianca Nicolosi [UNESP]; De Araujo Costa, Roberto Antonio [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (Springer Nature, 2017)
Background: In August 2011, the Specialized Center for Diabetes and Pregnancy of the Botucatu Medical School/Unesp adopted a new diagnostic protocol for gestational diabetes mellitus, recommended by the American Diabetes Association and the International Association of the Diabetes and Pregnancy Study Group. The glycemic profile was evaluated using the 75-g oral glucose tolerance test (OGTT) used to diagnose mild gestational hyperglycemia, recognized and treated in our department as gestational diabetes mellitus. The cost-effectiveness of the new guidelines and the continued need for the evaluation of the glycemic profile, as part of our Service protocol, are controversial and require further investigation. We aimed to assess the impact of the new guidelines on the evaluation of mild gestational hyperglycemia and gestational diabetes mellitus, the incidence of adverse perinatal outcomes, and the association between the 75-g OGTT and the glycemic profile for the diagnosis of mild gestational hyperglycemia. Methods: This cross-sectional study was performed identifying a convenience sample of pregnant women and their newborns. The women used our Service for diagnostic procedures, prenatal care and delivery, both before (January 2008 to August 14, 2011) and after (August 15, 2011 to December 2014) the protocol modification. The following variables were compared, following stratification according to diagnostic protocol: prevalence of gestational diabetes mellitus and mild gestational hyperglycemia, newborns large for gestational age, macrosomia, first cesarean delivery, and newborn hospital stay. Statistical analysis was performed using Poisson regression, the Student’s t test, the Chi square or Fisher’s exact test and risk estimate. The statistical significance threshold was set at 95% (p < 0.05). Results: The new protocol resulted in an 85% increase in the number of women with GDM, but failed to identify 17.3% of pregnant women classified as having mild gestational hyperglycemia, despite a normal 75-g OGTT. The new guidelines did not affect perinatal outcome. Conclusions: These results support the validity of maintaining the glycemic profile as part of the diagnostic protocol at our hospital. Large multicenter studies with an adequate sample size are required for conclusive evidence on the cost-effectiveness of the new protocol.
Keywords: Diagnosis; Gestational diabetes mellitus; Mild gestational hyperglycemia; Oral glucose tolerance test; Perinatal outcomes